GEO STRATEGI KEBIJAKAN LUAR NEGERI INDONESIA DI ERA JOKOWI DALAM PERSPEKTIF KONTRUKTIVISME - Fathun, Laode Muhamad (Universitas Muhammadiyah Yogyakarta, 2018)
This paper will explain the implementation of geostrategic policy of Indonesian foreign policy in constructivism approach. Constructivism has three basic arguments about identity, norms and language. Another geostrategic position is a way to achieve the objectives of the foreign policy policy of the country.Geostrategy is interpreted by the model of accommodation and corcondance to achieve the desired results. In practice the implementation of Indonesia’s foreign policy in crisis Rohingnya show the result that Indonsia proper use of its identity as, democracy, religion and unity. The argumentation is the constitutional and moral and cultural reasons so that Indonesia wants to get involved in the crisis. In the context of Indonesia’s engagement norm is any violation of the crisis that occurred in Myanmar is violating international norms as well as national norms due to human rights. On the other hand related to the Indonesian language using the approach of communication with the language of women’s diplomacy with women or the diplomacy of heart and heart so as to reduce conflict in Myanmar. The concrete form of Indonesia formulates diplomacy 4 + 1 with assistance such as education, economics, relief etc. Thus, hopefully this paper will add to the repertoire of knowledge related to the analysis of foreign policy